Parent Welcome Night to feature Pres. Castro - Uribes, Tom::::::::: (2013)
Parents of incoming Fresno State students will be greeted by University President Joseph I. Castro and other officials at Parent Welcome Night, 6 -8 pm. Tuesday, Aug.27, at the Smittcamp Alumni House courtyard.